BASİT İNKOMPLET SİNDAKTİLİNİN VEB FLEBİ İLE TEDAVİSİ: GREFTSİZ BİR YÖNTEM - AÇIKEL, Cengiz; ÜLKÜR, Ersin; EREN, Fikret; ÇELİKÖZ, Bahattin (Cerrahpaşa Medical Journal, 2014)
Background and Design.- In this clinical study, incomplete simple syndactyly that has sufficient distal web tissue was repaired without skin graft by a web flap on a subcutaneous tissue pedicle. The distally localized web flap was raised on its subcutaneous tissue pedicle and transferred proximally to form new web comissure while the syndactylous fingers were released by dorsal and volar longitudinal incisions. Raw surfaces on the fingers were primarily closed using unequal angled Z-plasties. Eighteen incomplete simple syndactylies on 15 hands (9 right hand, 6 left hand) of 13 male patients aging 20 to 22 years old were treated by the described method. The postoperative follow-up period ranged between 2 to 15 months (mean 8 months). Results.- Partial or full-thickness necroses were observed in two flaps that were raised from distal interphalangeal joint level. Aesthetic and functional results similar to normal web were achieved in the other cases. Main advantages of the method are; there is no problem inherent to skin grafts, the new web comissure is formed by a flap with similar quality, there is no incision on the distal edge of the created web, the raw surfaces of the fingers are lengthened and closed primarily by Z-plasties, and there is no flap donor site morbidity. Conclusion.- We conclude that the described method could effectively be used in the treatment of selected incomplete simple syndactyly cases.